The willingness of a society to act on behalf of Indigenous Australians and refugees: The role of contact, intergroup anxiety, prejudice and support for legislative change - Turoy-Smith, K.; Kane, Robert; Pedersen, A. (Wiley-Blackwell Publishing Inc., 2013)
The relationship between contact and prejudice against Indigenous Australians and refugees was explored. Using path analysis, increased quality of contact significantly decreased prejudice toward Indigenous Australians, both directly and indirectly through intergroup anxiety; while increased quantity of contact reduced prejudice via a direct pathway. Decreased levels of prejudice toward Indigenous Australians led to increases in support for legislation, which led to increases in willingness to act. Similar results were found for the refugee analysis, except that there was no relationship between quantity of contact and other variables. Qualitative analyses revealed the importance of context, the nature of experience and indirect experience, and societal factors. Our results indicate the power of contact, as well as other structural, interpersonal, and personal factors.